The Effect of Job Demands on Resilience in Honorary Employees - Nurshinta Dian Permatasari Hadjim; Agus Salim (Publikasi Indonesia, 2025)
Amid many job demands, honorary employees must have resilience and self-resilience so that they can survive and rise from all problems faced so that they can complete their responsibilities as employees. Self-resilience is called resilience. The job demands are called job demands. One of the factors that can affect resilience is the job demands given to honorary employees. This study was conducted to determine the effect of job demand on resilience in honorary employees. Using correlational quantitative research methods. The subjects in this study are honorary employees who work in government agencies of the Special Region of Yogyakarta with a sample of 104 people. The data collection technique carried out in this study is using a research scale. The scale of this study has been tested for reliability and validity. The research data was analyzed using classical assumption tests and hypothesis tests. The results of this study found that there was a very significant influence of job demands and resilience on honorary employees. This is shown by a significance value of 0.000 which indicates that the higher the job demands, the lower the resilience of honorary employees. The subject of this research is still limited to one area, therefore further research is expected to improve the findings or results of the research.